2016
DOI: 10.1159/000449032
|View full text |Cite
|
Sign up to set email alerts
|

Temporal Profile of Circulating microRNAs after Global Hypoxia-Ischemia in Newborn Piglets

Abstract: Background: There is a lack of reliable biomarkers that can identify and grade acute hypoxic-ischemic encephalopathy in newborns. MicroRNAs (miRNA) are short, non-coding strands of RNA that are released into the circulation in response to tissue stress and injury. Some miRNAs are highly tissue specific and thus may potentially be non-invasive biomarkers of neonatal hypoxic-ischemic brain injury. Objective: The aim of this study was to characterize the temporal expression of selected circulating miRNAs in a cli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 28 publications
2
20
0
Order By: Relevance
“…33 Few studies to date have examined miR-374a in neonatal HIE. A piglet model reported temporal changes in expression after injury 39 and a 2017 clinical HIE study confirmed downregulation in umbilical cord blood in neonatal HIE. 40 This study also reported the downregulation of miR-181b in infants with moderate and severe HIE and compared the predictive ability of miR-181b with biochemical and clinical markers in HIE (Table 4).…”
Section: Discussionmentioning
confidence: 92%
“…33 Few studies to date have examined miR-374a in neonatal HIE. A piglet model reported temporal changes in expression after injury 39 and a 2017 clinical HIE study confirmed downregulation in umbilical cord blood in neonatal HIE. 40 This study also reported the downregulation of miR-181b in infants with moderate and severe HIE and compared the predictive ability of miR-181b with biochemical and clinical markers in HIE (Table 4).…”
Section: Discussionmentioning
confidence: 92%
“…We acknowledge that not all miRNAs identified using our human cohort showed a change in HI piglets. Many clinical studies of miRNA alterations in HIE find our miRNAs of interest to be downregulated [ 5 , 56 ], while we and others have seen the opposite effect in animals [ 57 ]. It is unclear as to whether these are cross-species differences or whether it simply reflects the unpredictable nature and severity of HI in the clinical setting, as our porcine cohort received a uniform insult.…”
Section: Discussionmentioning
confidence: 99%
“…The physiological variables exhibited no significant differences at baseline between the hypoxia versus sham-operated control groups, for the parameters weight, pO 2 , pCO 2 , lactate, or BE [ 40 , 42 ]. Applying the fluorescence method for cfDNA estimation, piglets exposed to hypoxia exhibited a mean cfDNA level of 36.8±27.6 ng/ml at baseline (start of hypoxia) and an evident peak of 61.5±54.9 ng/ml at the end of hypoxia ( Table 2 and Fig 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…A total of n = 55 newborn piglets were included in the study at an age of 12–36 hours and in good general condition. All newborn piglets were anesthetized, ventilated, and surgically prepared, as previously described in detail [ 40 42 ]. Briefly, after approximately one hour of stabilization the intervention groups (n = 32 and n = 12) were exposed to global hypoxia for approximately 30–60 minutes and followed for 9.5 hours ( Fig 1 ).…”
Section: Methodsmentioning
confidence: 99%